3D Printed Bigel: A Novel Delivery System for Cannabidiol-Rich Hemp Extract - Anna Gościniak; Filip Kocaj; Anna Stasiłowicz-Krzemień; Marcin Szymański; Tomasz M. Karpiński; Judyta Cielecka-Piontek (Gels)
The therapeutic potential of Cannabis sativa L. extract has gained significant attention due to its diverse medical applications. Sublingual administration remains a common delivery method of cannabinoids; however, challenges often arise due to the inconvenient form of the extract and its taste. To address these issues, a novel bigel formulation was developed, combining water and oil phases to enhance stability and bioavailability. This formulation incorporates a cannabidiol-rich hemp extract, hyaluronic acid for its moisturizing properties, and a taste-masking agent to improve patient compliance and comfort. Using a standardized hemp extract rich in cannabinoids and a well-characterized terpene profile, the printability of the bigels was evaluated through 3D printing technology. A printout with known cannabidiol (CBD) and cannabidiolic acid (CBDA) content of 11.613 mg ± 0.192 of CBD and 4.732 mg ± 0.280 of CBDA in the printout was obtained. In addition, the release profile of CBD and CBDA was evaluated to determine the delivery efficiency of the active ingredient—dissolved active ingredient levels ranged from 74.84% ± 0.50 to 80.87% ± 3.20 for CBD and from 80.84 ± 1.33 to 98.31 ± 1.70 for CBDA depending on the formulation. Rheological studies were conducted to evaluate the viscosity of the bigels under varying temperature conditions, ensuring their stability and usability. Findings suggest that this 3D-printed bigel formulation could significantly enhance the delivery of cannabis extracts, offering a more convenient and effective therapeutic option for patients. This research underscores the importance of innovation in cannabinoid therapies and paves the way for further advancements in personalized medicine.